Menopausal hormone therapy and risk of venous thromboembolism: the story so far - Mohsen M.A. Abdelhafez; Karim A. M. Ahmed; Nashwa A.M. Ahmed; Mohd H. Ismail; Mohd Nazri Mohd Daud; Aya M. Eldiastey; Mohd Fariz Amri; Mohammad Saffree Jeffree; Fairrul Masnah @ Kadir; Dg Marshitah Pg Baharuddin; Mohammad Firdaus Bolong @ Mohd Darwis; Mohd Firdaus Hayati; et al. (African Journal of Reproductive Health/Women's Health and Action Research Centre (WHARC), 2024)
Menopausal hormone therapy (MHT) is known to increase the risk of venous thromboembolism (VTE), which includes deep vein thrombosis, pulmonary embolism, and less frequently cerebral vein thrombosis, but the absolute risk for a given patient is very low. After starting MHT, the risk of VTE seems to be at its highest, declining to the non-HRT user baseline level of risk after stopping. Whether estrogen-only or estrogen-progestin HRT combination is linked to a similar risk of VTE is unclear from the available evidence. The aim of this study is to evaluate the risks of developing VTE in relation to different types as well as different modes of administration of MHT through a database search including PubMed, MEDLINE, Google Scholar, Cochrane Library, and others in order to provide the women carers with the up-to-date and evidence-based guidelines and recommendations while counseling the post-menopausal women enquiring on use of hormonal therapies either to alleviate the menopausal symptoms or to prevent the longterm sequelae of estrogen deficiency.